Adherence to evidence-based guidelines for indwelling urinary catheter management: A cross-sectional study. Issue 5 (October 2021) - Coventry, Linda L.; Patton, Vicki; Whyte, Ashleigh; Liu, Xiaohua; Kaur, Hardeep; Job, Adina; King, Mary
Abstract: Background: Urinary tract infections from indwelling urinary catheters are amongst the most common healthcare acquired infection. Correct adherence to evidence-based guidelines has been shown to reduce these infections. There is limited Australian data on adherence to these guidelines. Aim: To examine the prevalence of use of indwelling urinary catheters and identify the rate of adherence to evidence-based guidelines. Methods: A cross-sectional study design using an audit tool was conducted at a major metropolitan teaching hospital (>600 beds) over 2-days in May 2019 in Western Australia. Findings: Prevalence of use of indwelling urinary catheters (n = 67 of 522 patients, 12.8%) was low. There was good compliance with observed catheter care apart from securement of the catheter. There was poor compliance with documenting the planned date for catheter removal and daily perineal/penile hygiene (2.9%–18.6%). Discussion: The observed care was generally compliant apart from securement. We attributed this to the possible lack of securement devices available on the general wards. Documentation was poorly completed at our centre and commonly reported in the literature. The introduction of prompting documentation using stickers may be useful in overcoming this shortfall in compliance. Conclusion: This audit will allow us to target areas for improvement in catheter care and ensuring accurate and complete documentation. More research is needed in obtaining information around the evidence-based guidelines and relationship to clinical development of catheter associated urinary tract infection.